2008
DOI: 10.1159/000161864
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Obesity and Elevated Blood Pressure as well as Onset of Puberty in German School Children Attending Different Educational Tracks

Abstract: Background:Obesity and associated comorbidities are increasingly evident in adolescents. This cross-sectional study investigates the relationship between educational level and prevalence of obesity, comorbidities, and onset of puberty in German schoolchildren. Subjects and Methods: 1,488 children from Leipzig attending different types of schools (‘Hauptschule’ or ‘Realschule’, HR, vs. ‘Gymnasium’, GYM) were examined for indices of obesity, pubertal stage and blood pressure. Results: Subjects attending HR had m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
1
1
0
2
Order By: Relevance
“…There was a significant relationship between age group and frequency of high blood pressure, with higher rates of hypertension in those aged 6-9 years and 10-12 years in this study. This is in agreement with one study in Germany [18]. Our study showed a statistically significant relationship between the presence of overweight/obesity and increased blood pressure in students.…”
Section: Discussionsupporting
confidence: 94%
“…There was a significant relationship between age group and frequency of high blood pressure, with higher rates of hypertension in those aged 6-9 years and 10-12 years in this study. This is in agreement with one study in Germany [18]. Our study showed a statistically significant relationship between the presence of overweight/obesity and increased blood pressure in students.…”
Section: Discussionsupporting
confidence: 94%
“…Prevalence of childhood overweight and obesity varies in industrialized countries between 15 and 35%, and the global epidemic has been increasing during the past decades (1–7). Metabolic and cardiovascular co‐morbidities of obesity are increasingly seen in young children, as by the age of 10 years, 60% of overweight children have at least one biochemical or clinical cardiovascular risk factor and 25% have more than two (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Esse achado encontrase em consonância com alguns estudos nacionais (BARBOSA et al, 2008;COSTA et al, 2007;JARDIM et al, 2007;LONGO et al, 2009;. Níveis elevados de IMC, CA e %G estão associados a hábitos sedentários e ao desequilíbrio nutricional (GELBRICH, BLÜHER, REICH, MÜLLER & KIESS, 2008). Desta forma, uma intervenção através de aumento dos níveis de atividade física diária, prática de exercícios físicos regulares e controle da ingestão calórica podem impactar positivamente esses fatores, diminuindo sua participação na gênese da HAS.…”
Section: Resultsunclassified